Status analysis and control measures of the debt risk in Chinese local government: based on the study of the relationship between “power, responsibility, and interests” - Xiaolin Miao (China Finance and Economic Review, 2016)
From the view of current conditions and developing trends of the debt scale in Chinese local government, the debt crisis will explode in the near future if it cannot be controlled in an effective way. According to the regional distribution in China, except for Beijing, Shanghai, Tianjin, and Hainan, the debt risk is mainly concentrated in the western region. In a further step, it can be seen that this risk of debt is resulted by the imbalanced relationship between "power, responsibility, and interests" which contains non-accordance of debt power (such as debt-financing power), confusion of debt responsibility (such as debt-management responsibility), and distortion of debt interests (such as private benefit and public interests). For this problem to be corrected, using the local government's debt for private interests should be prevented, realizing the local debt behavior takes to the "faithful" service for the public interests. To realize this purpose, it is important to monitor the relationship between "power, responsibility, and interests," which is the most important factor for setting up the debt risk control system of Chinese local governments. In particular, the control system should include the following aspects. First, it should find the right time to empower local government with debt power. Second, on the basis of both positive and negative sides, it should design a system to restrict the debt responsibility in local government, which is necessary to solve problems such as new debt, invalid debt, and overdue debt expansion. Third, it should propose the guidance mechanism to realize the convergence from the private benefit to the social interests on the local debt.
Keywords: 330; Local government debt; Risk control; "Power; responsibility; and interests" relationship